Pengaruh Customer Experience, Kualitas Produk, Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Produk Sepatu Eiger (Studi Kasus Pada Pengguna Sepatu Eiger Di Kecamatan Lowokwaru Kota Malang - Baihaqi, Moh Kholis; Arifin, Rois; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine and analyze the influence of customer experience, product quality, and customer satisfaction on Eiger shoe products (a case study on Eiger shoe users in Lowokwaru District, Malang City). Customer loyalty can be interpreted as a tool to assess the comparison between the quality and quantity of the company's product results that have been completed. This study is an explanatory research study with a quantitative approach, this study collected data from 75 respondents domiciled in Lowokwaru District, Malang City. The variables studied include customer experience, product quality, and customer satisfaction.The results of this study indicate that customer experience, product quality, and customer satisfaction have a significant effect on customer loyalty, customer experience has an effect on customer loyalty, product quality has an effect on customer loyalty, customer satisfaction has no effect on customer loyalty. This study suggests that companies continue to maintain and improve product quality, provide impressive customer experiences and satisfaction, and develop creative and relevant marketing strategies to current customer trends. Keywords: Customer Experience, Product Quality, Customer Satisfaction, Customer Loyalt